A Crime Fiction against the Murder of the Transcendent: Mario Levrero and a Program for the Subversion of the Genre - Blas Gabriel Rivadeneira (Catedral Tomada: Revista de Crítica Literaria Latinoamericana, 2022)
We propose a critical reading of the novels Nick Carter se divierte mientras el lector es asesinado y yo agonizo (1975), La banda del ciempiés (2010) and Dejen todo en mis manos (1996), which make up the crime trilogy, by Mario Levrero. The Uruguayan builds his figure as a "rare" author from the use of marginalized materials and disciplines, among them, the crime fiction that goes through his writing project. However, in a strategy of dissimulation, he points out it as a type of closed and commercial literature that closes the transformation of the reader. We argue that, through parody, display of artifice, or hyperbolic variants of paranoid fiction, Levrero sets out to subvert these boundaries. The writer appropriates the crime novel to develop another search which, while dismantling the protocols of the genre, enables its possibilities of modifying the subject. Against the crime of the transcendent by modern society that deprives the subject of luminous experiences, his poetics pursues contact with the Spirit or the Unconscious, interchangeable in his worldview. He thus manifests his program that conceives writing as a therapeutic device.